The Palm Walk, Botanic Gardens, Trinidad - (:unkn) unknown (Wilson Ltd., Trinidad, 2010)
A view of the Palm Walk in the Botanical Gardens in Port of Spain.
Colour: Sepia; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Palms--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Plants--Trinidad and Tobago; Garden walks--Trinidad and Tobago; Gardens--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain